Making Global Policy - Stone, Diane (Social Sciences, 2019)
This Element goes beyond traditional texts which focus on public policy as an activity of states to outline how global policy making has driven many global and regional transformations over the past quarter-century. This title is also available as Open Access on Cambridge Core.